The Missing Link: Telecommunications, Tropical Postmodernization, and the Production of Precarity in the Philippines, 1972–Present - Jaojoco, Patrick (Enquiry The ARCC Journal for Architectural Research, 2023)
For the vast majority of agricultural workers in the tenant peasantry class, the direct relation to a landscape valorized by a plantation economy is simultaneously a constantly mediated, ever-precarious economic relation to global capital. Since 1945, discourses of development have only deepened extractive and deeply unequal modes of governance and sociality in this context and across the Global South*. It is in this context that I aim to assess the politicized technics of precarity, weather prediction, and economics of agriculture in the Philippines under the authoritarian rule of Ferdinand Marcos. In studying the Philippines during its violent neoliberal transformation period, I hope to extract an ideal portrait of the environmental, technological, and economic logics of postcolonial globalization. To do so, I will assess a subtle yet crucial point in the Philippines’ history of science, technology, and the environment: the implementation of a meteorological telecommunications network and Marcos’s reordering of these stations as the Philippine Atmospheric, Geophysical and Astronomical Services Administration, or PAGASA (meaning “hope” in Tagalog). By understanding the several scales of political economy at work in direct relation to such a network, this paper seeks to illuminate the multiple dimensions of social instability rooted in the Philippine government’s neoliberal conflation of environment and economy. The architectures and technologies of network, then, highlight the numerous ways in which weather forecasting, agricultural production, and political control intersect in infrastructural development.